2022
DOI: 10.1016/s1473-3099(21)00421-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of co-administered ivermectin and albendazole in school-aged children and adults infected with Trichuris trichiura in Côte d'Ivoire, Laos, and Pemba Island, Tanzania: a double-blind, parallel-group, phase 3, randomised controlled trial

Abstract: Background Preventive chemotherapy with albendazole or mebendazole remains one of the cornerstones of soiltransmitted helminth control. However, these drugs are less effective against Trichuris trichiura. Combined ivermectin-albendazole is a promising treatment alternative, yet robust evidence is lacking. We aimed to demonstrate superiority of co-administered ivermectin-albendazole over albendazole monotherapy in three distinct epidemiological settings.Methods We conducted a double-blind, parallel-group, phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 23 publications
1
46
1
Order By: Relevance
“… The recent paper by Hurlimann et al Lancet Infect Dis. 2022 Jan;22(1):123-135 1 is an excellent example of several key points being made and would be worth citing. It reports three well designed and controlled clinical trials showing the higher efficacy of Ivermectin and albendazole combination therapy against T. trichiura and so is very relevant in the section on “improving evidence base for treatment regimes” when combination treatments are discussed.…”
mentioning
confidence: 99%
“… The recent paper by Hurlimann et al Lancet Infect Dis. 2022 Jan;22(1):123-135 1 is an excellent example of several key points being made and would be worth citing. It reports three well designed and controlled clinical trials showing the higher efficacy of Ivermectin and albendazole combination therapy against T. trichiura and so is very relevant in the section on “improving evidence base for treatment regimes” when combination treatments are discussed.…”
mentioning
confidence: 99%
“…Although the drivers and mechanisms underlying anthelmintic drug resistance in STH of human interest are incompletely understood, there is extensive data from the veterinary world where it is a widespread problem 43 . Moreover, a meta-analysis of randomized clinical trials against T. trichiura showed a temporal trend towards decreased efficacy of benzimidazole drugs and a recently published trial found lower efficacy of ALB in communities that have received MDA activities for more prolonged periods, suggesting drug resistance as a potential mechanism 10 , 44 . By using different mechanisms of action, ALB/IVM combinations provide regimens with a theoretical lower risk for the emergence of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that investigated the efficacy and safety of albendazole ivermectin co-administration (Hürlimann et al , 2022 1 , Welsche et al , 2021 2 , Keller et al , 2021 3 , Palmeirim et al , 2018 4 ) and as a consequence, there is no doubt, in my opinion, that a combination of albendazole plus ivermectin (in Fixed Dose Combination or dosed according to weight) is more efficacious than albendazole alone against T. trichiura and S. stercoralis (on the other side, no additional efficacy of the Fixed Dose Combination should be expected on hookworms).…”
mentioning
confidence: 99%
“…Of note, only 10 years ago, hookworm was the predominant STH species in Côte d’Ivoire [ 23 ]. T. trichiura has since become predominant in our study areas, which may also be a result of the current drug regimens used during PC (i.e., single dose of albendazole and mebendazole), which show limited efficacy against this species [ 44 ]. Additionally, the identified hotspots need special attention for factors hindering effective control, such as impaired drinking water source management (e.g., Ahouya cluster) and geographic obstacles for sanitation improvement (e.g., Tiagba with high ground water levels and direct sewage drainage into the surrounding waterbodies).…”
Section: Discussionmentioning
confidence: 99%